Scaling up access to HIV pre-exposure prophylaxis (PrEP): should nurses do the job?. Issue 5 (May 2022) - Schmidt, Heather-Marie A; Schaefer, Robin; Nguyen, Van Thi Thuy; Radebe, Mopo; Sued, Omar; Rodolph, Michelle; Ford, Nathan; Baggaley, Rachel
Summary: Task sharing has been one of the most important enabling policies supporting the global expansion of access to HIV testing and treatment. The WHO public health approach, which relies on delivery of antiretroviral therapy (ART) by nurses, has enabled a trebling of the number of people receiving ART during the past decade. WHO recognises that HIV pre-exposure prophylaxis (PrEP) can also be provided by nurses; however, many countries still do not have policies in place that support nurse provision of PrEP. In sub-Saharan Africa, most countries allow nurses to prescribe ART, but only a few countries have policies in place that allow nurses to prescribe PrEP. Nurse-led PrEP delivery is particularly low in the Asia-Pacific region, which has some of the world's fastest growing epidemics. Even in many high-income countries, PrEP scale-up has been limited because policies often require medical doctors or specialists to prescribe. Service providers in many countries are coming to realise that scaling up access to PrEP cannot be achieved by medical doctors alone, and nurse-led PrEP delivery can help to lay the groundwork for supporting uptake of other HIV prevention approaches that will become available in the future. Countries with policies that authorise nurses to prescribe ART could be early adopters and help to pave the way for wider adoption of nurse-led PrEP delivery.